Senhores e trabalhadores no Cariri cearense: terra, trabalho e conflitos na segunda metade do século XIX - Reis Júnior, Darlan de Oliveira (2014)
This thesis discusses the relations between masters and workers who lived in the region of Cariri, located in the extreme south of the Province of Ceará, in the second half of the nineteenth century. The regional area domain occurred not only by natural resources appropriation, such as control of the land, but also through the development of a speech on economic vocation of the place and exploitation of free and enslaved workers, in different economic activities. In an approach based on the field of Social History, I intend to analyze the issues implicating the labor world: contradictions arising from social inequality, control practices established by masters, as well as the conflicts and different forms of workers resistance. Were used sources such as newspapers, laws, criminal cases, civil cases, inventories, correspondences and reports of public authorities.